Cyberlaw and Students: A Comprehensive Study - Effendi, Muhammad Imam; Purwaningsih, Sri Budi; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This curated dataset, sourced from Lens.org, compiles 120 journal articles exploring Cyberlaw's intersection with students. Leveraging specific filters, 9 law-focused articles were meticulously selected. The primary goal was to provide a comprehensive view of Cyberlaw's global landscape concerning student populations. Analyzing active institutions, prolific authors, and key publications highlighted South Africa's significant contribution and shed light on the intricate relationship between legal frameworks and students' digital activities. Notable trends across publication years were identified, including influential works such as L. Lessig's 1999 publication, "The Law of the Horse: What Cyberlaw Might Teach." This dataset serves as a valuable resource for researchers seeking insights into Cyberlaw's dynamics concerning student communities worldwide. Highlights : Curated dataset of 120 articles on Cyberlaw and Students Emphasis on the relationship between legal frameworks and students' digital activities Valuable insights for understanding Cyberlaw dynamics within student contexts Keywords: Cyberlaw, Students, Dataset, Legal Frameworks, Digital Activities